Implementasi Pendekatan Pembelajaran Mendalam Materi Unggah-Ungguh Bahasa Jawa Siswa SD Negeri Kademangan 1 - Sunarti; Surayanah (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
This qualitative case study addresses the degradation of Unggah-ungguh (Javanese etiquette) among students, often caused by the shift toward informal Indonesian slang. Research at SDN Kademangan 1, Blitar, explores the planning, execution, and impact of a Deep Learning approach based on social learning theory. By utilizing the role-playing method, the study aims to create a conscious, meaningful, and engaging learning experience. Data collected through observations, interviews, and tests reveal that while the approach successfully fosters cultural awareness and student engagement, the primary challenge remains minor student anxiety during classroom performances.